PROLIFERASI DINASTI POLITIK DI KABUPATEN KUANTAN SINGINGI TAHUN 2010-2020 - Nindi Safitri Permana; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Political dynasty is understood as a form of control of power in government at the local level. A political dynasty in the traditional political sense is which the rulers seek place their families, brothers and relatives in strategic positions whit the goal of building a political empire whitin government. This effort is made with the purpose of those who become members of the political dynasty will keep one another in power (executive, legislative or judicial). Putting a family or brother in positions of stress will make it easier for a ruler to control and control all the things a ruler needs (Agustino, 2014). The goal of this study is to find out ho the use of poer for political dynasties in the district of the Kuantan Singingi 2010-2020. The study involves a qualitative approach. The research location is conducted in Kuantan Singingi district, and data collection techniques are done with interviews and documentation. The result of this study was the us of power to develop the political dynasy of H. Sukarmis in Kuantan Singingi regency through his power in the Golkar party then spread to the position pf the DPRD and then to the position of the Regent. The Sukarmis family took control of the government, the economy and began to spread to community organizations such as the Golkar, KNPI, Tarbiya-perti and have patron-client relationships. This power is used to develop and defend the political dynasty in the district of Kuantan Singingi. Keywords: Proliferation, Power, Dynasty Politics